2017
DOI: 10.1002/jcp.26135
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3‐kinase inhibition potentiates glucocorticoid response in B‐cell acute lymphoblastic leukemia

Abstract: Despite remarkable progress in polychemotherapy protocols, pediatric B-cell acute lymphoblastic leukemia (B-ALL) remains fatal in around 20% of cases. Hence, novel targeted therapies are needed for patients with poor prognosis. Glucocorticoids (GCs) are drugs commonly administrated for B-ALL treatment. Activation of the phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin signaling pathway is frequently observed in B-ALL and contributes to GC-resistance. Here, we analyzed for the first time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…It is well established that the PI3K/Akt/mTOR pathway is aberrantly activated in approximately 60% of T‐ALL patients (Silva et al, ) and correlates with a poor outcome (Bongiovanni et al, ). Our group previously showed that PI3K inhibition displayed strong cytotoxic effects on both ALL cell lines and primary cells, demonstrating that targeting PI3K could be an attractive strategy for treating ALLs (Bressanin et al, ; Evangelisti et al, ; Lonetti et al, ; Lonetti et al, ). This therapeutic approach for ALL has been supported by several clinical trials of PI3K inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that the PI3K/Akt/mTOR pathway is aberrantly activated in approximately 60% of T‐ALL patients (Silva et al, ) and correlates with a poor outcome (Bongiovanni et al, ). Our group previously showed that PI3K inhibition displayed strong cytotoxic effects on both ALL cell lines and primary cells, demonstrating that targeting PI3K could be an attractive strategy for treating ALLs (Bressanin et al, ; Evangelisti et al, ; Lonetti et al, ; Lonetti et al, ). This therapeutic approach for ALL has been supported by several clinical trials of PI3K inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (Evangelisti et al, ). Cells were lysed using M‐PER Mammalian Protein Extraction Reagent supplemented with the Protease and Phosphatase Inhibitor Cocktail (Thermo Fisher Scientific Inc., Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that ZSTK‐474, a pan p110 PI3K inhibitor, displayed the most powerful cytotoxic effects in B‐ALL cells. However, both ZSTK‐474 and the dual γ/δ p110 PI3K inhibitor IPI‐145 (Duvelisib), sensitized B‐ALL cells to DEX by restoring nuclear translocation of the GC receptor and counteracted stromal cell‐induced DEX‐resistance (Evangelisti et al, ). Moreover, we performed gene expression analysis which demonstrated that the combination consisting of ZSTK‐474 and DEX strengthened the DEX‐induced up‐ or downregulation of several genes involved in apoptosis, however the combination also rescued the effects of genes that might be involved in GC‐resistance.…”
Section: Pi3k Inhibitorsmentioning
confidence: 99%
“…ALL is most commonly a pediatric malignancy, but a significant percentage of cases occurs also in adults (Evangelisti et al, ). Although pediatric ALL is highly responsive to chemotherapy, relapse occurs in approximately 25% of children (Pica et al, ).…”
Section: Introductionmentioning
confidence: 99%